Leda Papastefanaki, Η φλέβα της γης: Τα μεταλλεία της Ελλάδας, 19ος–20ός αιώνας [The vein of the earth: The mines of Greece, 19th–20th centuries] - Karampatsos, Christos (Historein, 2021)
Review of Leda Papastefanaki. Η φλέβα της γης: Τα μεταλλεία της Ελλάδας, 19ος–20ός αιώνας [The vein of the earth: The mines of Greece, 19th–20th centuries]. Athens: Vivliorama, 2017. 392 pp.